2017
DOI: 10.3982/ecta13239
|View full text |Cite
|
Sign up to set email alerts
|

Partial Ambiguity

Abstract: We extend Ellsberg's two‐urn paradox and propose three symmetric forms of partial ambiguity by limiting the possible compositions in a deck of 100 red and black cards in three ways. Interval ambiguity involves a symmetric range of 50 − n to 50 + n red cards. Complementarily, disjoint ambiguity arises from two nonintersecting intervals of 0 to n and 100 − n to 100 red cards. Two‐point ambiguity involves n or 100 − n red cards. We investigate experimentally attitudes towards partial ambiguity and the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 40 publications
6
36
1
Order By: Relevance
“…Cubitt et al (2017) find that the smooth ambiguity model explains their subjects' ambiguity preferences better than α-maxmin, an SDW model. Chew et al (2017) interpret their data as supporting the model of Ergin and Gul (2009), an SDU model. On the other hand, the data in Baillon and Bleichrodt (2015) are most consistent with two SDW models, prospect theory and, to a lesser extent, α-maxmin.…”
Section: Box 1 Introduction To Ambiguitymentioning
confidence: 74%
See 1 more Smart Citation
“…Cubitt et al (2017) find that the smooth ambiguity model explains their subjects' ambiguity preferences better than α-maxmin, an SDW model. Chew et al (2017) interpret their data as supporting the model of Ergin and Gul (2009), an SDU model. On the other hand, the data in Baillon and Bleichrodt (2015) are most consistent with two SDW models, prospect theory and, to a lesser extent, α-maxmin.…”
Section: Box 1 Introduction To Ambiguitymentioning
confidence: 74%
“…A popular SDW model is prospect theory (Kahneman & Tversky, 1979;Tversky & Kahneman, 1992). The empirical literature is divided as to which of these models best describes people's ambiguity preferences (Baillon & Bleichrodt, 2015;Cubitt et al, 2017;Chew, Miao, & Zhong, 2017). Cubitt et al (2017) find that the smooth ambiguity model explains their subjects' ambiguity preferences better than α-maxmin, an SDW model.…”
Section: Box 1 Introduction To Ambiguitymentioning
confidence: 99%
“…The empirical literature gives no clear answer which ambiguity model best describes people's preferences. While the results in Cubitt et al (forthcoming) are consistent with the smooth model, Baillon and Bleichrodt (2015) and Chew et al (2017) observed that models like Choquet expected utility (Schmeidler 1989) and α-maxmin (Ghirardato et al 2004) could better explain their data. In this section we explore the robustness of our results under the neo-additive model of Chateauneuf et al (2007).…”
Section: Neo-additive Preferencesmentioning
confidence: 77%
“…Under "partial ambiguity", the probability is defined in the interval [0.25, 0.75], reducing the interval size by half. Two levels of ambiguity are implemented because ambiguity aversion has been shown to increase with the size of the probability interval (Chew et al, 2017). This variation allows us to test whether this behavioral difference also exists for excuse-driven behavior.…”
Section: Lotteriesmentioning
confidence: 99%